2019
DOI: 10.1002/ceat.201800527
|View full text |Cite
|
Sign up to set email alerts
|

Acid Hydrolysis of Chitosan to Oligomers Using Hydrochloric Acid

Abstract: The natural polymer chitosan is widely used for medical and drug delivery applications. Low molecular weight chitosan (LMWC) has superior properties compared to high molecular weight chitosan (HMWC), which open new applications of LMWC, especially in the cosmetics, food, and pharmaceutical industries. LMWC is often produced from HMWC by acid, enzymatic, or oxidative hydrolysis. Industrially, hydrolysis with dilute HCl is preferred, since it is simple, practical, and gives a high yield. In this study 2M HCl was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…To overcome these limitations, chitosan hydrolysis by acids, mainly acetic acid [9], nitrous acid [22], phosphoric acid, hydrogen uoride [8] and hydrochloric acid (HCl) [23,11] has been evaluated as simple, easy and practical method. Industrially, acid hydrolysis with HCl is preferred, since it is relatively simple, easy, practical and gives a high yield [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To overcome these limitations, chitosan hydrolysis by acids, mainly acetic acid [9], nitrous acid [22], phosphoric acid, hydrogen uoride [8] and hydrochloric acid (HCl) [23,11] has been evaluated as simple, easy and practical method. Industrially, acid hydrolysis with HCl is preferred, since it is relatively simple, easy, practical and gives a high yield [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It is previously reported that HCl not only breaks the glycosidic bonds in chitosan chains but also hydrolyzes the Nacetyl amide groups to give chitosan chains with lower Mw and AD. Indeed, the acid concentration, the reaction time and the used temperature are considered among the most crucial factors of the acid hydrolysis process [23,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations